2021
DOI: 10.3390/nu13093072
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Adolescent Afghan Refugees Living in Peshawar, Pakistan

Abstract: Pakistan has hosted millions of Afghan refugees over the last several decades. Due to poor socioeconomic status, food insecurity and inadequate access to health care, these refugees are considered to be at high risk of malnutrition. Previous studies on nutritional assessment of high-risk populations (refugees) have focused mainly on women and children (0–59 months). The current study aims to assess nutritional status of adolescent Afghan refugees; the population who are equally vulnerable to malnutrition and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
4
14
1
Order By: Relevance
“…Figure 1 shows a bar graph of family size and frequencies based on their BMI. where stunting, thinness, and overweight and obesity were 35.3%, 4.4%, and 14.8%, respectively, as underweight ratio is also high in this research study (Saeedullah et al, 2021).…”
Section: Sociodemographic Statussupporting
confidence: 55%
See 1 more Smart Citation
“…Figure 1 shows a bar graph of family size and frequencies based on their BMI. where stunting, thinness, and overweight and obesity were 35.3%, 4.4%, and 14.8%, respectively, as underweight ratio is also high in this research study (Saeedullah et al, 2021).…”
Section: Sociodemographic Statussupporting
confidence: 55%
“…Malnutrition is the unhealthy condition of body due to imbalance of energy or nutrients (Aylward et al, 2021 ), and malnourished girls will eventually be malnourished mothers in future (Ahmed & Haboubi, 2010 ); also they have preterm births because of their poor nutritional status (Badshah et al, 2008 ). Refugees face a high risk of malnutrition due to poor socioeconomic status, food insecurity, and insufficient health‐care facility (Saeedullah et al, 2021 ). Malnutrition is directly or indirectly responsible for maternal mortality and is particularly high in Afghanistan (Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among the adolescent Afghan refugees living in a refugee camp in Peshawar, Pakistan reported that the participants were suffering from stunting, thinness and overweight and obesity. 12 Similar scenerio were found among the adolescents from Syrian refugee families living in Turkey and North Korean refugee families living in South Korea. 13 14 Double burden of malnutrition can result in detrimental outcome in any impoverished community by increasing the burden of non-communicable diseases in future.…”
Section: Discussionsupporting
confidence: 55%
“…Presence of double burden of malnutrition is not unique to this refugee adolescent group. A study conducted among the adolescent Afghan refugees living in a refugee camp in Peshawar, Pakistan reported that the participants were suffering from stunting, thinness and overweight and obesity 12. Similar scenerio were found among the adolescents from Syrian refugee families living in Turkey and North Korean refugee families living in South Korea 13 14.…”
Section: Discussionmentioning
confidence: 69%
“…A key finding is that from 1990 to 2019, the age-standardized incidence rates of overall nutritional deficiency and the protein–energy malnutrition subcategory showed the greatest increases in males in Afghanistan. This could be attributable to the war in Afghanistan that has led to a lack of safe water and sanitation, poor quality housing, poor nutrition, and limited access to quality health services ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%